2018
DOI: 10.4315/0362-028x.jfp-18-078
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Safety of Fresh Tilapia (Oreochromis niloticus) from Kenyan Fresh Water Fish Value Chains

Abstract: This study evaluated the microbiological safety of fresh Nile tilapia (Oreochromis niloticus) from Kenyan fresh water fish value chains. One hundred seventy-six fish samples were analyzed. The microbial counts of hygiene indicators, total viable aerobic count (TVC), total coliforms, and fecal coliforms isolated by using culture techniques were enumerated, and microbial pathogens present in the fish samples were identified and characterized by using molecular methods. The diversity of bacterial isolates was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The total viable counts (TVC) observed in this study was lower compared to the findings of Adedeji et al (2012), Hilary et al (2018) and Ogunleye et al (2021). Bacteria of public health importance were isolated, however, the TVC did not exceed 10 5 CFU/g approved by FAO (1979).…”
Section: Discussioncontrasting
confidence: 80%
“…The total viable counts (TVC) observed in this study was lower compared to the findings of Adedeji et al (2012), Hilary et al (2018) and Ogunleye et al (2021). Bacteria of public health importance were isolated, however, the TVC did not exceed 10 5 CFU/g approved by FAO (1979).…”
Section: Discussioncontrasting
confidence: 80%
“…After a gavage of L. monocytogenes into the stomachs of live salmon, they were readily cleared without pathologic changes to the animals within three days [ 66 ], and rainbow trout held in fish farms where L. monocytogenes was detected in the water were rarely positive for L. monocytogenes [ 68 ]. A recent study [ 61 ] demonstrated an increase in the L. monocytogenes contamination level in tilapia from capture (1.2%) to the domestic market (5.8%). Taken together, these data suggest that fish may become transient asymptomatic carriers of L. monocytogenes after exposure but are not likely to be long-term spreaders of the pathogen.…”
Section: Carriage Of L Monocytogenes By Wild Animalsmentioning
confidence: 99%
“…For example, handling tilapia was reported associated with Vibrio vulnificus outbreak in Seattle supermarket [18]. Other foodborne pathogenic bacteria including Salmonella enterica, enteropathogenic Escherichia coli, Listeria monocytogenes, Yersinia enterocolitica, and Klebsiella pneumoniae were identified from fresh Nile tilapia in Kenyan fresh water fish chains [19]. Shigatoxigenic and enteropathogenic Escherichia coli were isolated from farmed tilapia fish (Oreochromis niloticus) in northeast region of Sao Paulo state [20].…”
Section: Introductionmentioning
confidence: 99%